Asymmetric Response of Sea Surface Salinity to Extreme Positive and Negative Indian Ocean Dipole in the Southern Tropical Indian Ocean. Issue 11 (29th October 2022) - Sun, Qiwei; Zhang, Yuhong; Du, Yan; Jiang, Xingwei
Abstract: Based on the Argo and multi‐satellite observations, this study investigates the asymmetric response of sea surface salinity (SSS) to two extreme positive and negative Indian Ocean Dipole (IOD) events in the southern tropical Indian Ocean (TIO). During positive IOD events, the easterly wind anomalies trigger zonal freshwater advection along the equator, decreasing SSS, while cold sea surface temperature (SST) depress the convective precipitation in the southeastern TIO (SETIO), increasing the SSS. Contrast SSS anomalies along the equator and in the SETIO show opposite phases during positive and negative IOD events. These SSS anomalies have enhanced in recent years, reaching the strongest in the extreme negative IOD in 2016 and positive IOD in 2019. The case study shows that positive SSS anomalies occurred in the southern TIO during both positive and negative IOD events in 2016 and 2019, suggesting significant asymmetry in SSS. Analysis of the mixed layer salinity budget shows that the local precipitation and the entrainment associated with the upwelling Rossby waves played an essential role in the SSS increase in 2016, while the decreased precipitation and horizontal advection caused by the westward South Equatorial Current contributed to the SSS increase in 2019. Further analyses suggest that SSS response is more sensitive to thermocline shoaling than deepening, and SSS response to precipitation is greater at shallower mixed layer than at deeper ones, which is the main reason for the asymmetric response of the SSS to negative and positive IOD events. Plain Language Summary: Indian Ocean Dipole (IOD) is one of the leading climate modes in the Indian Ocean, which impacts changes in temperature, precipitation, and salinity. This study reveals significant asymmetric responses in SSS during the decay phase of positive and negative IOD events. During the mature phase of positive and negative IOD events, there are opposite changes in sea surface temperature, atmospheric circulation, rainfall, and SSS in the equatorial and southeastern tropical Indian Ocean (SETIO). However, SSS increases in the SETIO during the decay phase of both positive and negative IOD events, revealing an asymmetric feature. This asymmetric structure of SSS anomalies has strengthened recently and reached extremes in the 2016 negative IOD event and the 2019 positive IOD event. The upwelling (downwelling) Rossby waves play an important role in the asymmetric response of SSS anomalies in the southern TIO since the SSS response is more sensitive to thermocline shoaling than deepening, and the shallower mixed layer may imply the SSS response to precipitation anomaly. Key Points: Contrast sea surface salinity (SSS) anomalies occur in the equatorial and southeastern tropical Indian Ocean (TIO) during the mature phases of Indian Ocean Dipole (IOD) SSS anomalies are out of phase during positive and negative IOD events but show an asymmetric change in the southern TIO The asymmetry is due to different SSS responses to precipitation and thermocline changes associated with the ocean Rossby waves